2020
DOI: 10.1038/s41598-020-77362-x
|View full text |Cite
|
Sign up to set email alerts
|

Both proliferation and lipogenesis of brown adipocytes contribute to postnatal brown adipose tissue growth in mice

Abstract: Brown adipose tissue (BAT) is the primary non-shivering thermogenesis organ in mammals, which plays essential roles in maintaining the body temperature of infants. Although the development of BAT during embryogenesis has been well addressed in rodents, how BAT grows after birth remains unknown. Using mouse interscapular BAT (iBAT) as an example, we studied the cellular and molecular mechanisms that regulate postnatal BAT growth. By analyzing the developmental dynamics of brown adipocytes (BAs), we found that B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…In contrast, altricial species are born with little or no BAT, whose deposition increases when exposed to low temperatures during the first weeks of birth [ 75 ], and they are the primary source of metabolic heat [ 66 ]. In mice ( Mus musculus ), this happens at approximately two weeks of birth [ 76 ]. Analysis from days 0 to 120 after birth has reported that the interscapular BAT’s weight increases from approximately 10 mg to almost 60 mg, respectively, to be replaced later by WAT [ 77 ].…”
Section: Morphoanatomical Differences Associated With Thermoregulatio...mentioning
confidence: 99%
“…In contrast, altricial species are born with little or no BAT, whose deposition increases when exposed to low temperatures during the first weeks of birth [ 75 ], and they are the primary source of metabolic heat [ 66 ]. In mice ( Mus musculus ), this happens at approximately two weeks of birth [ 76 ]. Analysis from days 0 to 120 after birth has reported that the interscapular BAT’s weight increases from approximately 10 mg to almost 60 mg, respectively, to be replaced later by WAT [ 77 ].…”
Section: Morphoanatomical Differences Associated With Thermoregulatio...mentioning
confidence: 99%
“…Immediately at birth, pups have to be able to defend body temperature. After birth, brown adipose tissue still grows, mainly due to proliferation until postnatal day 14 and thereafter by storing more lipid ( 20 ), a transition suggestively synchronous to the observed whitening ( 14 ).…”
Section: Adipose Tissue Development and Plasticitymentioning
confidence: 99%
“…As plausible as this interpretation sounds, it fails to explain a simultaneous whitening of brown adipose tissues, if these two transitions are in fact causally connected. Both types of adipose tissue undergo postnatal developmental stages possibly accounting for the observed remodeling events: although functional at birth, BAT continues growth by an initial postnatal phase of rapid precursor proliferation and subsequent terminal differentiation including triglyceride loading ( 20 ). At the turning point, these events may be misinterpreted as whitening of existing brown adipocytes.…”
Section: Potential Physiological Purposes Of Postnatal Adipose Tissue...mentioning
confidence: 99%
“…At 1 month, and later in life, buccal fat pad is instead made of WAT, characterized by larger adipocytes [ 65 ]. It remains unclear whether brown cells transform into white adipocytes or the WAT develops in the empty spaces once the BAT disappeared at the level of buccal fat pad, but it has been demonstrated that in mice BAT growth at the level of the inter scapular region in the first two weeks of life is due to both proliferation and lipogenesis, while later in infancy BAT grows mainly via lipogenesis [ 67 ]. While BAT develops in embryos, BeAT is induced from WAT during postnatal life [ 68 ].…”
Section: Bat In Term and Preterm Infants Childhood And Adolescencementioning
confidence: 99%